2018
DOI: 10.3390/jof5010001
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ptn1, a PTEN/TEP1 Orthologue, in Ustilago maydis Reduces Pathogenicity and Teliospore Development

Abstract: The PTEN/PI3K/mTOR signal transduction pathway is involved in the regulation of biological processes such as metabolism, cell growth, cell proliferation, and apoptosis. This pathway has been extensively studied in mammals, leading to the conclusion that PTEN is a major tumor suppressor gene. PTEN orthologues have been characterized in a variety of organisms, both vertebrates and non-vertebrates, and studies of the associated PTEN/PI3K/mTOR pathway indicate that it is widely conserved. Studies in fungal systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…Both tepA deletion and overexpression strains were found to be indistinguishable from WT in their hyphal growth rate and colony morphology, a result similar to what has been observed for deletion of this gene in F. graminearum and U. maydis (Vijayakrishnapillai et al, 2018;Zhang et al, 2010). TEM analysis revealed that the S. pombe tep1 deletion mutant has an abnormal vacuolar morphology, highlighting the subtle nature of some culture phenotypes (Mitra et al, 2004).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Both tepA deletion and overexpression strains were found to be indistinguishable from WT in their hyphal growth rate and colony morphology, a result similar to what has been observed for deletion of this gene in F. graminearum and U. maydis (Vijayakrishnapillai et al, 2018;Zhang et al, 2010). TEM analysis revealed that the S. pombe tep1 deletion mutant has an abnormal vacuolar morphology, highlighting the subtle nature of some culture phenotypes (Mitra et al, 2004).…”
Section: Discussionsupporting
confidence: 66%
“…In previous studies, deletion of the PTEN homologues in F. graminearum and U. maydis resulted in a decrease in virulence on wheat and maize, respectively (Vijayakrishnapillai et al, 2018;Zhang et al, 2010). Here we found that L. perenne plants infected with the tepA deletion mutant of E. festucae and scored 10 weeks postinoculation, were not consistently significantly different from WT-infected plants in leaf length and tiller number (Figs 7, S8).…”
Section: Overexpression Of Epichloë Festucae Mssd or Tepa Does Not Afmentioning
confidence: 90%
See 2 more Smart Citations
“…For example, Heymont et al (2000) showed that the phosphatase gene ScTEP1 reduces the ability of S. cerevisiae to sporulate by affecting its process of meiosis, which is accompanied by a decrease in the accumulation of dityrosine, a major component of the yeast cell wall. In addition, the deletion of the related PTPs genes FgTEP1 in F. graminearum or UmPtn1 in U. maydis also affect the formation of spores in these pathogenic fungi ( Zhang et al, 2010 ; Vijayakrishnapillai et al, 2018 ). Although we still do not know the specific reasons for the decrease in conidial production caused by the deletion of CgPTPM1 , based on the results of previous studies, we hypothesized that this gene may be involved in some signaling pathways that result in the reduction of conidiation.…”
Section: Discussionmentioning
confidence: 99%